2017
DOI: 10.3389/fnins.2017.00122
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Hypothalamic Gene Expression during Daily Torpor in Djungarian Hamsters (Phodopus sungorus)

Abstract: Animals living at high or temperate latitudes are challenged by extensive changes in environmental conditions over seasons. Djungarian hamsters (Phodopus sungorus) are able to cope with extremely cold ambient temperatures and food scarcity in winter by expressing spontaneous daily torpor. Daily torpor is a circadian controlled voluntary reduction of metabolism that can reduce energy expenditure by up to 65% when used frequently. In the past decades it has become more and more apparent, that the hypothalamus is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…It was previously shown that the expression of Col1a1 and C ol3a1 genes was definitely observed in the pituitary glands of rats in the cells surrounding the capillaries, which are supposed to be the basic components of ECM [57]. Interestingly, similar to our results, the transcriptome analysis of hypothalamic gene expression during daily torpor in Djungarian hamsters revealed upregulation of the Col18a1, Col5a3, Col17a1, and Col20a1 genes, which was specific for torpor as compared to normothermic hamsters [58]. Based on these data, one might preliminarily have hypothesized that the Col genes are involved in natural regulation, for example, of physiological adaptation under repeated stress in mice, winter torpor in hamsters, or CNS pathologies.…”
Section: Resultssupporting
confidence: 88%
“…It was previously shown that the expression of Col1a1 and C ol3a1 genes was definitely observed in the pituitary glands of rats in the cells surrounding the capillaries, which are supposed to be the basic components of ECM [57]. Interestingly, similar to our results, the transcriptome analysis of hypothalamic gene expression during daily torpor in Djungarian hamsters revealed upregulation of the Col18a1, Col5a3, Col17a1, and Col20a1 genes, which was specific for torpor as compared to normothermic hamsters [58]. Based on these data, one might preliminarily have hypothesized that the Col genes are involved in natural regulation, for example, of physiological adaptation under repeated stress in mice, winter torpor in hamsters, or CNS pathologies.…”
Section: Resultssupporting
confidence: 88%
“…It was previously shown that mRNA expression for the Col1a1 and Col3a1 genes was distinctly observed in pituitary glands of rats in cells located around capillaries in the gland and were supposed to be the main components of the ECM [Fujiwara et al 2010]. Interestingly, in the hypothalamus of Djungarian hamsters, transcriptome analysis revealed upregulation of the Col18a1 and Col5a3 similar with our results, and increase of the Col17a1, Col20a1 and Col26a1 gene expression, which were specific for torpor in comparison with normothermic hamsters [Cubuk et al 2017]. The preliminary hypothesis from this part of data may be the recognition of involvement Col* genes into natural regulation, for example, of physiological adaptation under repeated stress in mice, winter torpor in hamsters, or CNS pathologies associated with collagens during neurodevelopment [Ali et al 1998;Cheng et al 2009;Lepelletier, et al 2017].…”
Section: Resultssupporting
confidence: 90%
“…Hypothalamic blocks were cut from frozen brain samples as described in Cubuk et al ., 2017[43]. Hypothalamic samples were homogenized in 1 ml TriFast by using a micropestle.…”
Section: Methodsmentioning
confidence: 99%
“…All primers were designed on P . sungorus specific sequences obtained from our previous Illumina study [43]. 18–25 bp long primers were designed using the online tool OligoAnalyzer 3.1 with a melting temperature of 60°C ± 1.1°C.…”
Section: Methodsmentioning
confidence: 99%